Application of Local Fractional Variational Iteration Method for Solving Fredholm integral equations Involving Local Fractional Operators - Jassim, Hassan Kamil; Kadhim, Hussein Khashan (University of Thi-Qar Journal, 2019)
In this paper, the local fractional variational iteration method (LFVIM) is used for solving linear and nonlinear Fredholm integral equations of the second kind within local fractional derivative operators. To illustrate the ability and simplicity of the method, some examples are provided. The results reveal that the proposed method is very effective and simple and it leads to the exact solution.